Enhancement of TNF-α induced antiproliferation in human cervical cancer cells by extracts from Thai medicinal plants - C. Managit (2018)
Human cervical cancer is known to be a dreadful disease with high resistance to chemotherapeutic drugs in clinical use. Natural products are valuable sources for development of anticancer agents. Many plant-derived anticancer compounds were reported to modulate signal transduction pathway associated with cell proliferation and apoptosis. One well-known pathway is via the enhancement of TNF-α, a cytokine that can induce apoptotic cell death and inhibit tumorigenesis. The purpose of this study is to evaluate TNF-α antiproliferative synergistic activity of Thai medicinal plant extracts. The antiproliferative effects were determined in human cervical cancer (HeLa) cells using WST-1 cell proliferating assay. Among twenty six different tested extracts at the concentration of 30 μg ml-1, 95% ethanolic extract from stems of Derris scandens, aqueous extract from leaves of Azadirachta indica, aqueous extract from leaves of A. indica var. siamensis and 95% ethanolic extract from roots of Amomum biflorum significantly decreased viability of HeLa cells treated with TNF-α (20 ng/ml). However, only 95% ethanolic extract from roots of A. biflorum combined with TNF-α significantly decreased viability of HeLa cells to 70.96±2.25% cell viability, when compared to cell viability of HeLa cells treated with only plant extract (93.84±10.73%). Data suggested that this plant extract enhanced TNF-α antiproliferative activity in HeLa cells and it has potential for further development as chemotherapeutic agent for anticancer therapy via the enhancement of TNF-α induced apoptosis of cancer cells. © ISHS.